Potensi Minyak Sereh Wangi (Cymbopogon nardus) sebagai Antibakteri terhadap Propionibacterium acnes dan Staphylococcus aureus pada Sediaan Gel Antijerawat - Kania Apenta Olisvelos; Dwi Aditiyarini; Aniek Prasetyaningsih (Pro-Life, 2023)
Acne can be caused by the bacteria Propionibacterium acnes and Staphylococcus aureus. One way to treat acne is to use antibiotics. However, this can create resistance. In this study, citronella oil will be formulated into an anti-acne gel preparation with various concentrations of 10%, 15% and 20%. The study began with distillation of citronella oil and analysis and identification of compounds. Then the gel was made by mixing citronella oil in the HPMC gel base and then the gel preparation was tested for antibacterial activity by the disc diffusion method and physical preparation tests included organoleptic tests, pH measurements, viscosity tests, homogeneity tests, dispersion tests, gel stability tests. Based on the results of compound analysis using GC-MS, citronella oil contains geraniol (55.05%). Of the three formulations, the preparation that has good gel physical properties based on its physical properties is F2 with 15% citronella oil content. In the antibacterial test, the results showed that citronella oil gel had the ability to inhibit Propionibacterium acnes and Staphylococcus aureus with the most optimal formulation being F2 with an average inhibition of 1.5 cm.